High‐resolution imaging of magnetisation transfer and nuclear Overhauser effect in the human visual cortex at 7 T. (26th June 2013) - Mougin, Olivier; Clemence, Matthew; Peters, Andrew; Pitiot, Alain; Gowland, Penny
Abstract : The aim of this study was to optimise a pulse sequence for high‐resolution imaging sensitive to the effects of conventional macromolecular magnetisation transfer (MT m ) and nuclear Overhauser enhancement (NOE), and to use it to investigate variations in these parameters across the cerebral cortex. A high‐spatial‐resolution magnetisation transfer‐prepared turbo field echo (MT‐TFE) sequence was designed to have high sensitivity to MT m and NOE effects, whilst being robust to B 0 and B 1 inhomogeneities, and producing a good point spread function across the cortex. This was achieved by optimising the saturation and imaging components of the sequence using simulations based on the Bloch equations, including exchange and an image simulator. This was used to study variations in these parameters across the cortex. Using the sequence designed to be sensitive to NOE and MT m, a variation in signals corresponding to a variation in MT m and NOE across the cortex, consistent with a reduction in myelination from the white matter surface to the pial surface of the cortex, was observed. In regions in which the stria was visible on T 2 *‐weighted images, it could also be detected in signals sensitive to MT m and NOE. There was greater variation in signals sensitive to NOE, suggesting that the NOE signal is more sensitive to myelination. A sequence has been designed to image variations in MT m and NOE at high spatial resolution and has been used to investigate variations in contrast in these parameters across the cortex. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : A magnetisation transfer (MT) sequence was designed to study the variation in MT and nuclear Overhauser enhancement (NOE) across the cortex, and showed changes consistent with the variation in myelination across the cortex. In regions in which the stria of Gennari was visible on T 2 *‐weighted images, it could also be detected in signals sensitive to MT, and there was greater variation in signals sensitive to NOE, suggesting that the NOE signal is more sensitive to myelination.